CANOPY STRUCTURE PREFERENCE FOR THE HABITAT OF JAVAN LANGUR (PRESBYTIS COMATA DESMAREST 1822) IN MOUNT CIREMAI NATIONAL PARK - Larasati, Adhisty
Javan langur is an endemic primate from West Java. Javan langur’s life depends highly on forest canopy (arboreal). Potential danger from land degradation caused by encroachment could change the structure of its habitat, especially the vegetation cover. Until now, there hasn’t been much information regarding the effects of vegetation structure change to Javan Langur. Thus, this research was conducted to identify the canopy structure prefered by javan langur population in Mount Ciremai National Park. The activity was done by observing canopy density (CD), branch-free height (BH), total height (TH), canopy thickness (CT) and tree architectural model based on the observed behaviours of javan langur. CD was identified with the hemispherical photography method, as for the canopy characteristic was identified through direct measurements on the field and literary study. In general, the study found that javan langur do their activities within tree canopy with CD from 62,200 – 83,637% on the average of 76,966%, then BH of 6,375 – 9,357 m, TH of 16,980 - 20,250 m, CT of 8,764 – 18 m and the architectural model of Roux. Javan langur with mobile behaviours were found on higher BH, while the immobile behaviours were found on higher TH and CT. Generally, it could be concluded that javan langur are relatively more often found in primary forest ecosystem with medium to high CD, relatively thick canopy and with canopy strata of C to B.